2011
DOI: 10.1111/j.1475-6773.2010.01236.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Telephone with World Wide Web-Based Responses by Parents and Teens to a Follow-Up Survey after Injury

Abstract: Objective. To identify sociodemographic factors associated with completing a followup survey about health status on the web versus by telephone, and to examine differences in reported health-related quality of life by method of response. Data Sources/Study Settings. Survey about child health status of 896 parents of children aged 0-17 years treated in a hospital emergency department or admitted for a traumatic brain injury or arm injury, and 227 injured adolescents aged 14-17 years. Study Design. The main outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Similar to other Canadian studies, we also found that Internet respondents reported higher incomes and more education [27,38]. Other studies have found younger age, higher incomes, greater education, and race to be strongly associated with the Internet and email access [6,39-41]. Although we do not know whether that telephone respondents in our study have access to the Internet, our results are consistent with what these findings suggest about Internet access.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to other Canadian studies, we also found that Internet respondents reported higher incomes and more education [27,38]. Other studies have found younger age, higher incomes, greater education, and race to be strongly associated with the Internet and email access [6,39-41]. Although we do not know whether that telephone respondents in our study have access to the Internet, our results are consistent with what these findings suggest about Internet access.…”
Section: Discussionsupporting
confidence: 89%
“…The fieldwork for this survey was conducted via the Internet by Authentic Response (AR) web panel company, which consists of approximately 4,000,000 registered members. Although some research has suggested that web-based surveys may be biased with respect to measuring health outcomes (Rivara et al, 2011), other studies have suggested that web-based administration is comparable to other modes with respect to respondents’ demographics and reported health behavior risks (Fricker et al, 2005; McMorris et al, 2009). To improve data validity, AR includes panel members by invitation only and uses algorithms to identify and exclude professional survey-takers.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers would ideally take steps to minimize nonresponse bias during the study design phase. For example, techniques aimed at increasing response rates include techniques such as different and multiple survey modes (e.g., mail vs. telephone vs. internet; Baines et al 2007;Beebe et al 2007;Fowler et al 2002;Nicholls et al 2011;Rivara et al 2011), incentives for participation (Deehan et al 1997;Halpern et al 2002Halpern et al , 2011, cognitive interviewing (Willis, DeMaio, and Harris-Kojetin 1999), and highlighting the match between the survey and potential participants' interests (Groves, Cialdini, and Couper 1992). Along these lines, funders and sponsors of research should help play a role by understanding that their investment will hold less value if the researcher is unable to address nonresponse bias prior to data collection.…”
Section: Defining Nonresponse Biasmentioning
confidence: 99%